Measuring the Concentrations of Heavy Elements in Some Human Organs (Breast, Thyroid Gland, and Uterus) Affected by Cancer in Thi-Qar Governorate - Fadhel Abbas; Ahmed Mathloom (مجلة علوم ذي قار, 2025)
Heavy elements are one of the three causes of cancer. Heavy elements in cancerous tissues from certain organs (breast, thyroid, and uterus) are measured. 36 samples were collected from malignant and benign tumors divided into three groups, 12 samples for each one (breast, thyroid, and uterus), consisting of six affected samples and six healthy samples. Measurements were conducted using an inductively coupled plasma mass spectrometry (ICP-MS) device for heavy metals such as Bi, Co, Cr, Cu, Ni, Sr, Mn, and Mo. The current study recorded the highest concentration of strontium in breast cancer patients and the lowest cobalt concentration. It was found that there was a decrease in bismuth, cobalt, and nickel in cancerous tissues compared to benign tissues. At the same time, all other elements increased in cancerous tissues compared to healthy tissues. In the thyroid, the highest concentration was Sr , and the lowest was Ni.  It was found that Bi, Cr, and Sr had low values in affected tissues compared to healthy tissues, while all other elements increased in cancerous tissues compared to healthy ones. In the uterus, the highest concentration was also strontium , and the lowest was molybdenum. There was a decrease in bismuth and copper in cancerous tissues compared to healthy ones, while all other elements increased at a value of p < 0.05.